2022
DOI: 10.29327/5106561
|View full text |Cite
|
Sign up to set email alerts
|

Assistência Dos Profissionais De Saúde Às Mulheres Frente À Realização Do Aborto Ilegal: Uma Revisão Integrativa

Abstract: O Livro Saúde da Mulher surgiu como um projeto que engloba as principais doenças e abordagens terapêuticas da medicina voltada ao sexo feminino. Uma ampla discussão foi criada na escolha e desenvolvimento dos capítulos que estariam presentes nesta primeira edição. Com todo esse cuidado, o livro apresenta uma leitura fluida, organizada em uma sequência lógica, o que facilita a compreensão do estudante ou profissional da área. Portanto, esta primeira edição espera fornecer conhecimento para os leitores, sejam el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Stress during critical neurodevelopmental periods may lead to a glutamatergic overdrive onto PV interneurons, potentially changing the balance of E/I in cortical and limbic circuits that support multiple behaviors [34][35][36] . Common molecular features of numerous animal models to study SCZ include a reduced number of PV interneurons 37 . However, our previous metaanalysis revealed that only a few studies analyzed the impact of adolescent stress on the hippocampal PV interneurons 37 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stress during critical neurodevelopmental periods may lead to a glutamatergic overdrive onto PV interneurons, potentially changing the balance of E/I in cortical and limbic circuits that support multiple behaviors [34][35][36] . Common molecular features of numerous animal models to study SCZ include a reduced number of PV interneurons 37 . However, our previous metaanalysis revealed that only a few studies analyzed the impact of adolescent stress on the hippocampal PV interneurons 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Common molecular features of numerous animal models to study SCZ include a reduced number of PV interneurons 37 . However, our previous metaanalysis revealed that only a few studies analyzed the impact of adolescent stress on the hippocampal PV interneurons 37 . Abnormal PV interneuron function is thought to lead to vHip hyperactivity, resulting in a hyperdopaminergic state 38 , a condition consistent with clinical observations in SCZ 39,40 .…”
Section: Discussionmentioning
confidence: 99%